Don't kill the goose that lays the golden eggs: Strategic delay in project completion - Svetlana Katolnik; Jens Robert Schöndube (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2014)
It's puzzling that most projects fail to complete within the predetermined timeframe given that timing considerations rank among the major goals in project management. We argue that when managers can extract private benefits from working on a project, project delay becomes optimal. We introduce a continuous-time framework for project management activities that incorporates this feature. A manager's unobserved effort cumulatively increases the project's success probability, but decreases the expected duration of the project and with it the expected flow of on-the-job benefits. A strict deadline limits incentives for effort delay, but also decreases the probability that the project will be terminated in due time. In this trade-off, the optimal deadline balances the increase in expected project value against the expected increase in project duration and costs. Since the manager does not want to 'kill the golden goose' prematurely, he always prefers a stricter deadline compared to the principal. As a result, project completion is threatened by both effort provision over time and contractual agreements on time.
Keywords: D82; M52; 330; Optimal deadline; Dynamic incentives; Strategic delay; Project completion